Design and Transmission Analysis of Compound Connecting Rod Type Pineapple Picking Device - Xiaofei Liu; Xinghua Gao; Yabo Wei (Jixie chuandong)
In order to solve the problems of high labor intensity， difficulty in picking， and low efficiency of manual pineapple picking， a pineapple picking device based on crank slider， offset linear sliding rod and multi-link transmission mechanism is designed. The Adams is used to simulate and analyze the movement of the mechanism， and the parameters of each component of the device are optimized. The actual prototype has been tested， and the results show that the device is suitable for picking pineapples with a stem diameter of 3-6 cm. The test statistics show that the single picking time of the device is 1.2 s less than manual picking， and the efficiency is increased by 26%. The stationary motion of the device and the cutting stability of the tool are also verified.